Pemanfaatan Sistem Informasi Desa Berbasis Website untuk Meningkatkan Akses Informasi Publik, Transparansi Pemerintahan, dan Efisiensi Pelayanan Masyarakat - Alfry Aristo Jansen Sinlae; G. Melva Kurniaramadhan Adhia Lengary; Maria Chapriany Prima Angela; Vebrianti Trysinde Missa; Judeit Paulina Soares; Eduarda Babo Gomes; Yustina Abuk; Putri Kusuma Dewi (Journal of Social Responsibility Projects by Higher Education Forum, 2025)
Digital transformation has become a critical requirement for supporting transparent, participatory, and public-service-oriented village governance. Uitiuh Tuan Village, in Semau Selatan Subdistrict, Kupang Regency, is developing as a destination for religious and nature tourism and therefore requires digital platforms capable of supporting the dissemination of public information, ensuring transparency in development, and promoting the village’s potential. This community service initiative aims to develop a website-based village information system and enhance the capacity of village officials in managing digital information. The methods employed include partner needs analysis, website design and development, training and mentoring for village officials, and program monitoring and evaluation. The activity involved 10 participants, including village officials, BUMDes managers, tourism managers, and representatives of the village youth. The results showed that participants’ average proficiency increased from 41.6% before the activity to 87.8% afterward, representing a 46.2% improvement. The participant satisfaction rate reached 93.4%, indicating that the program was very well received by the partners. The developed website has been successfully used as a medium for public information, government transparency, community services, and promoting the village’s tourism potential. Thus, this community service activity has made a tangible contribution to strengthening digital-based village governance and supports the development of Uitiuh Tuan Village toward becoming a sustainable Smart Village.